Irish film and television The Year in Review -2020 - Roddy Flynn (Estudios Irlandeses, 2021)
Part of the appeal of cinema-going since its inception, especially with the emergence of purpose built picture palaces designed to appeal to more well-heeled patrons, has been the opportunity to seal oneself into a dark, womb-like environment and succumb the stimulation of the optical and auditory senses by high definition images and crystal clear sounds. In an era of Covid-19, those positives have become major disincentives to cinema-going. There have been no documented cases of Coronus Virus transmission occurring within an Irish cinema. Nonetheless, given the zombie movie-esque culture of fear, which has transformed our perception of strangers into potential vectors of transmission, how dedicated a cinephile would one need to be to contemplate entering a closed room shared with others even under socially-distanced conditions, with decent ventilation and mandatory mask-wearing?